Diseño y construcción de un sistema de calentamiento de agua potable con una capacidad de 60 l/día, mediante el uso de energía solar para una vivienda unipersonal - Cajo Andaluz, Carlos Adrian (2017)
Solar energy is one of the most reliable resources to ensure energy security. It´s known that the amount of solar energy that reaches the surface of the earth could supply all the energy needs of the planet. This technical project proposes the generation of sanitary hot water associated with solar energy for the heating of water, developing the corresponding calculations to obtain the greatest efficiency the machine to realize. Previous research has shown that thermosiphon solar heaters have very high efficiencies since. In the installed thermosiphon system, it was determined that with an area of 1. 3 m covers the need of 60 l / day. On June 30 this year reaches a temperature of 91 ˚C for a period of 4 hours, whereby at the last point of consumption a temperature higher than 60 ˚C is obtained and the temperature of 53 ˚C is recorded as the Lowest on the 6th day of operation. Once the thermosiphon tests have been performed, a cost analysis is performed that results in the system being viable with a low investment compared to the system profitability. It is determined that the system in 4 years and 2 months begins to generate profits, additional maintenance the low costs so the system durability is prolonged.